Development of an Augmented Reality Training Environment Construction System Using Puzzle-Like Programming in a Real Environment - Harazono, Yuki; Tamura, Taichi; Omoto, Yusuke; Ishii, Hirotake; Shimoda, Hiroshi; Tanaka, Yoshiaki; Takahashi, Yoshiyuki (International Journal of Human–Computer Interaction, 2024)
Emergency drills and drills against terrorism have been held at nuclear facilities. Shortcomings of these drills are that the numbers of emergency scenarios and roles are limited because many workers must participate in them simultaneously. The times during which all employees can participate simultaneously are limited. As a means of solving these problems, augmented reality (AR) training has been increasingly adopted in recent years, but difficulties of creating contents and the inadequate degrees of freedom in the created contents are becoming problematic. For this study, we developed an AR training environment construction system for users to create scenarios easily by simply assembling and placing blocks representing scenario components in a real-world environment. To realize the construction system, we also developed the "Program Block," which enables users to create scenarios in a puzzle-like style. The system can create and simulate various scenarios involving interaction between trainees and a real-world environment. To evaluate the ease of system usage and flexibility for scenario creation, a subjective experiment was conducted at a nuclear facility. Results indicate that users can construct an AR training environment easily.